Humanizing Learning in the AI Era: Teachers Efforts to Cultivate Learning Awareness and Independent Thinking in Students of SMAN 2 Singingi Hilir - Hasnah Faizah; Rahma Luthfiyyah AD; R. Lulu Sri Maifonika; Reni Rama Yenni; Musaroh S.; Ria Indrawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Advances in artificial intelligence (AI) technology present both opportunities and challenges for education. On the one hand, AI can enrich the learning process; on the other hand, it has the potential to shift human values ​​in education. This study aims to describe teachers' efforts to humanize learning in the AI ​​era, particularly in fostering students' learning awareness and independent thinking at SMAN 2 Singingi Hilir. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis was conducted following the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that teachers act as facilitators and inspirators in technology-based learning. Humanization of learning is realized through instilling the values ​​of reflection, empathy, and responsibility in the use of AI. In addition, teachers foster students' independent thinking through project-based learning and reflective discussions that balance digital intelligence with moral values. This process helps students become critical, independent, and ethical learners amidst the digitalization of education.